Google trends, una herramienta útil para detectar la presencia de polen atmosférico - Oteros, José (2015)
Pollinosis is one of the most extended allergies in the world, determining directly the quality of life of the population. Airborne pollen forecasting has become a key objective for allergists and aerobiologists trying to prevent the symptoms of hay fever. Google trends is a tool developed by Google, which provides information about the dynamics of user searches through internet. The main aim of this work is to conduct a preliminary assessment of the usefulness of this tool to detect the presence of large concentrations of pollen in the atmosphere and to explore the impact of pollinosis among the population. To achieve these objectives, the analysis is based on data for olive pollen concentrations in the atmosphere of Cordoba (Spain) and search counts in Google of the words "Allergy", "Pollen" and "Olive". We observed a high correlation and a high geographic relationship between the number of searches for words related to pollen allergy, and the actual concentrations of atmospheric pollen. This tool possesses a great potential in the fight against allergy because it can provide instant and on-line information about symptoms in population, unlike traditional methods that have a mismatch of information. Thus, the present study provides evidence about the potential of Google trends to detect the presence of aeroallergens and to study the impact of pollinosis.